2022
DOI: 10.1186/s12903-022-02606-3
|View full text |Cite
|
Sign up to set email alerts
|

Dental anomalies and their therapeutic implications: retrospective assessment of a frequent finding in patients with cleft lip and palate

Abstract: Background Orofacial clefts are characterized by a frequent occurrence of dental anomalies. Numerous studies demonstrate the high prevalence of dental aplasia, supernumerary teeth, and hypoplastic teeth in patients with cleft lip with/without cleft palate (CL/P), yet the therapeutic consequences are rarely discussed. This study explores prevalence, localization, and association between primary and secondary dentition in a large European collective and begins to evaluate the significance of dent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Therefore, utilization of the zebrafish model to study the development of genetic mechanisms involved in craniofacial abnormalities is recommended for future studies. Because dental anomalies are highly associated with cleft lip and palate, well-designed studies on zebrafish dentition may offer new findings in the dental field [ 44 , 45 ]. It has been reported that zebrafish tooth structures are similar to mammalian teeth, which justifies their use to study human dental abnormalities ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, utilization of the zebrafish model to study the development of genetic mechanisms involved in craniofacial abnormalities is recommended for future studies. Because dental anomalies are highly associated with cleft lip and palate, well-designed studies on zebrafish dentition may offer new findings in the dental field [ 44 , 45 ]. It has been reported that zebrafish tooth structures are similar to mammalian teeth, which justifies their use to study human dental abnormalities ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, we observed that agenesis of the non-cleft lateral incisor reduced the odds of achieving favourable treatment outcomes in terms of the PM but not the DAR, even if the association approached statistical significance. Missing lateral incisors were found to predispose UCLP children to maxillary hypoplasia and to increase the need for orthodontic treatment and orthognathic surgery [ 19 , 57 , 58 ]; the main problem is the maxillary asymmetry favouring the development of cross-bite.…”
Section: Discussionmentioning
confidence: 99%
“…However, children with CL/P are likely to possess dental and jaw deformities; this may lead to inaccurate estimation. The prevalence of dental anomalies has been shown to vary significantly depending on the type and severity of the cleft, including numeric abnormalities such as missing and supernumerary teeth, morphological abnormalities, such as microdontia and fusing teeth, and tooth replacement abnormalities [11,12]. Furthermore, it has been reported that enamel defects are more common in CL/P patients than in non-CL/P individuals [13].…”
Section: Introductionmentioning
confidence: 99%